Analisis Kemampuan Pemecahan Masalah Matematika Pada Siswa Kelas VIII SMPN 3 Woha Bima Semester Ganjil Tahun Ajaran 2021/2022 - Ainun Rizqi; Arjudin Arjudin; Muhammad Turmuzi; Syahrul Azmi (Griya Journal of Mathematics Education and Application, 2022)
The research is purpose to description skill level of mathematical problem solving in grade students of junior high school 3 Woha Bima odd semester in academic year 2021/2022. This type of research is descriptive research. The subjects in this study were 36 students of VIII B class at SMPN 3 Woha Bima. Analisys techniques in this research is using essay test with aljabar subject as much 3 number questions with measure ability of student mathematical problem solving it can be categorized in 3 category, which is high category, medium category, and low category. After categoryzed the students will be interviewed for deeped the answer on the questions. In the interview step students will be choosed each 2 students to represent each category ability of problem solving so at the interviewed the researcher will be interview to 6 students for deeped the answer that they are got where the interview do after the researcher group each students into the category and will be choosed each 2 students to represent each category. Result of the result in the students with high ability problem solving are 14 students (39%) , medium ability problem solving are 16 students (44%), and low ability problem solving are 6 students (17%).